2014
DOI: 10.3389/fmicb.2014.00288
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of antimicrobial use in food-producing animals

Abstract: Benefits and risks of antimicrobial drugs, used in food-producing animals, continue to be complex and controversial issues. This review comprehensively presents the benefits of antimicrobials drugs regarding control of animal diseases, protection of public health, enhancement of animal production, improvement of environment, and effects of the drugs on biogas production and public health associated with antimicrobial resistance. The positive and negative impacts, due to ban issue of antimicrobial agents used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
183
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(202 citation statements)
references
References 100 publications
(132 reference statements)
2
183
0
4
Order By: Relevance
“…The term 'antibiotic growth promoter' is used to define any agent that either destroys or inhibits bacteria when administered at a small, sub-therapeutic dose (Hao et al, 2014). The greater use of several antibiotics for growth promotion purpose has arisen due to the popularity and necessity of poultry farming.…”
Section: Introductionmentioning
confidence: 99%
“…The term 'antibiotic growth promoter' is used to define any agent that either destroys or inhibits bacteria when administered at a small, sub-therapeutic dose (Hao et al, 2014). The greater use of several antibiotics for growth promotion purpose has arisen due to the popularity and necessity of poultry farming.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that cover a range of issues including but not limited to the uncertainties about the use of antibiotics in food animals and the risk posed to human health [62,63]; the epidemiological and molecular evidence for the spread of resistance from food animals to man [53,60,61,64]; and the benefits and risks of antimicrobial use in food-producing animals [65,66]. Despite the numerous studies focused on these issues, the WHO surveillance report (2014) indicated that there are major gaps associated with the surveillance and sharing of data around resistance in foodborne bacteria and its relationship with animal and human health [4].…”
Section: Food Safetymentioning
confidence: 99%
“…Despite the numerous studies focused on these issues, the WHO surveillance report (2014) indicated that there are major gaps associated with the surveillance and sharing of data around resistance in foodborne bacteria and its relationship with animal and human health [4]. The benefits and risks of the use of antibiotics in the food animals remain a complex issue, and present a major challenge, and appear to be a double-edged sword [66]. This section touches briefly on some of the continued challenges for food safety.…”
Section: Food Safetymentioning
confidence: 99%
“…Enrofloxacin and its active metabolite Ciprofloxacin, fluoroquinolone antibiotic, which have been approved for use in food animals and are effective against organisms resistant to commonly used antibiotics in veterinary medicine such as β-lactams, aminoglycosides, tetracyclines and macrolides (Hao et al, 2014). Drug residues may pass on to tissues and milk due to extra label use of these antibiotics.…”
Section: Introductionmentioning
confidence: 99%